"Our flight suits are not just plain blue": The co-production of coordination and bodies in a military air display squadron. Issue 11 (November 2022) - Bouty, Isabelle; Godé, Cécile
While prior investigations of organizational coordination have mainly focused on cognitive processes, this article brings the physical and symbolic body more centrally into the phenomenon. Mobilizing the 'strong' practice programme, we explore how organizational coordination practice and bodies co-produce each other. Our study is an empirical qualitative analysis of Patrouille de France, a military air display squadron. By successively zooming in and out from pilots' doings and sayings, we reveal three body-related threads (training, sensitizing and distinguishing) by which organizational coordination and bodies co-produce each other. We especially point to technical and physical capital, proprioception, kinaesthesia, embodied awareness of co-presence and the symbolic (re)presentation of bodies as embodied aspects of the actors' habitus structured by and for coordination. Our findings have implications for our understanding of organizational coordination by showing that there is more to bodies in coordination than just embodied cognition or communication. They also further coordination literature by emphasizing that coordination practice includes organizationally structured bodywork aimed at enhancing bodies; bodywork that is not limited to learning the practice but crucial to maintaining actors in that practice.